A first quantitative census of vascular epiphytes in rain forests of Colombian amazonia (2005)
ABSTRACT: Epiphytism in Colombian Amazonia was described by counting vascular epiphytes in thirty 0.025-ha (5 · 50 m) plots, well-distributed over the main landscape units in the middle Caqueta´ area of Colombian Amazonia. Each plot was directly adjacent to a 0.1-ha plot at which the species composition of trees and lianas (diameter at breast height (DBH) ‡ 2.5 cm) had been recorded 3 years earlier. The purpose of the study was to explore abundance, diversity, and distribution of epiphytes between the principal landscape units. A total of 6129 individual vascular epiphytes were recorded belonging to 27 families, 73 genera, and 213 species (which included 59 morpho-species). Araceae, Orchidaceae, and Bromeliaceae were the most speciose and abundant families. A total of 2763 phorophytes were registered, 1701 (62%) of which with DBH ‡ 2.5 cm. About 40–60% of the woody plants with DBH ‡ 2.5 cm carried epiphytes, which points at low phorophyte limitation throughout all landscapes. Epiphytism was concentrated on stem bases. Just as trees, epiphyte species assemblages were well associated with the main landscapes. Contrary to trees, however, epiphyte abundance and diversity (species richness, Fisher’s alpha index) hardly differed between the landscapes. This calls for caution when explanations for distribution and dynamics of tree species are extrapolated to growth forms with a totally different ecology.